Crosstalk Between Polygonatum kingianum, the miRNA, and Gut Microbiota in the Regulation of Lipid Metabolism - Jincai Dong; Jincai Dong; Wen Gu; Xingxin Yang; Linxi Zeng; Xi Wang; Jiankang Mu; Yanfang Wang; Fengjiao Li; Min Yang; Jie Yu (Frontiers Media S.A., 2021)
Objectives:Polygonatum kingianum is a medicinal herb used in various traditional Chinese medicine formulations. The polysaccharide fraction of P. kingianum can reduce insulin resistance and restore the gut microbiota in a rat model of aberrant lipid metabolism by down regulating miR-122. The aim of this study was to further elucidate the effect of P. kingianum on lipid metabolism, and the roles of specific miRNAs and the gut microbiota.Key findings:P. kingianum administration significantly altered the abundance of 29 gut microbes and 27 differentially expressed miRNAs (DEMs). Several aberrantly expressed miRNAs closely related to lipid metabolism were identified, of which some were associated with specific gut microbiota. MiR-484 in particular was identified as the core factor involved in the therapeutic effects of P. kingianum. We hypothesize that the miR-484-Bacteroides/Roseburia axis acts as an important bridge hub that connects the entire miRNA-gut microbiota network. In addition, we observed that Parabacteroides and Bacillus correlated significantly with several miRNAs, including miR-484, miR-122-5p, miR-184 and miR-378b.Summary:P. kingianum alleviates lipid metabolism disorder by targeting the network of key miRNAs and the gut microbiota.